Analisis Kemampuan Komunikasi Matematis Siswa SMP pada Materi Bangun Ruang Sisi Datar - Herlina Dwi Cahyani; Agung Prasetyo Abadi (Journal on Education, 2023)
In order to better understand how junior high school pupils solve arithmetic issues involving flat sided spaces, this study will examine their mathematical communication abilities. At SMPN 3 Tirtajaya, this research was done. There are five measures of students' ability to communicate mathematically, including the first measure, which links visuals to mathematical ideas, the second measure, which makes conjectures, gathers evidence, and formulates definitions and generalizations, the third measure, which expresses ideas, situations, and mathematical relations with visuals, the fourth measure, which turns everyday events into mathematical situations, and the fifth measure, which explains and creates q. A descriptive qualitative research methodology was used to perform the study on 21 students in class IX. The test asks students to answer five questions regarding how well they can communicate mathematical ideas. The description test method is the method utilized to collect data. According to the data analysis's findings, pupils at SMPN 3 Tirtajaya are classed as having moderate problem-solving skills.